Efficacy of fermented foods in irritable bowel syndrome: a systematic review and meta-analysis of randomized controlled trials - Ding, Liang; Duan, Jinnan; Yang, Tao; Yuan, Mengping; Ma, A. Huo; Qin, Yuehua (Frontiers in Nutrition, 2025)
ObjectiveFermented foods (FFs) may theoretically benefit irritable bowel syndrome (IBS) symptoms, but the role of FFs for IBS patients in the real world is inconsistent and has not been systematically assessed. We performed a systematic review and meta-analysis to examine this issue.MethodsPubMed, MEDLINE, Embase and Cochrane Library databases were searched up to August 2024. Randomized controlled trials (RCTs) investigating the efficacy of FFs in IBS were eligible for the analysis. Two authors independently screened studies and extracted data. Data were pooled using relative risk (RR) of dichotomous data and standardized mean difference (SMD) for continuous data.ResultsA total of 16 RCTs with 1,264 IBS patients were included. There were 12 RCTs involving 975 patients providing primary outcomes which was defined as symptom relief. The proportion of symptom relief was associated with the administration of FFs (RR 1.22, 95% CI 1.04–1.42, p = 0.01, I2 = 0%). For secondary outcomes, FFs also exerted a beneficial effect on global symptoms scores (SMD = −0.15; 95% CI −0.29 to −0.02, p = 0.02, I2 = 46%), but no significant improvement on abdominal pain scores and bloating scores. Subgroup analysis showed that fermented milk had a beneficial effect on symptom relief (RR 1.19, 95% CI 1.01 to 1.39, p = 0.04, I2 = 0%).ConclusionFermented foods, especially fermented milk with probiotics properties, appear to be efficacious in irritable bowel syndrome. However, given the limitations of current evidence, this conclusion should be interpreted with caution.Systematic Review RegistrationThis study was registered on the International Prospective Register of Systematic Reviews (PROSPERO) as CRD42024576608.